Estabelecimento de fungos nematófagos aplicados no campo para o controle dos nematoides-chaves dos citros no Brasil - Martinelli, Paulo Roberto Pala [UNESP]; dos Santos, Jaime Maia [UNESP]; Soares, Pedro Luiz Martins [UNESP] (My University, 2012)
Monitoring the survival of nematophagous fungi is needed to establish periods of reapplication of formulations of nematophagous fungi to control the citrus nematode in the field. We monitored the survival of fungi: Arthrobotrys robusta, A. oligospora, A. musiformis Dactylella leptospora and Monacrosporium eudermatum in plots treated with 1, 2, 4, 6 liters of the formulation of fungi/plant or witness without the application, during the period of nine months with the first assessment six months after application and the other with intervals of three months after the first evaluation. The fungus D. leptospora was found only in the evaluation of 6 months after treatment application, indicated a short survival time in the soil. However, the isolated A. robusta, A. musiformis and A. oligospora were recovered in all evaluations and especially in plots treated with higher doses of the formulation and witness. Monacrosporium eudermatum was recovered in all experimental periods and even in assessing the witness portion of nine months after application. The fact of the presence of species of Arthrobotrys and M. eudermatum in control plots indicates that native species that were already orchard.

O monitoramento da sobrevivência de fungos nematófagos se torna necessária para estabelecer períodos de reaplicação de formulações de fungos nematófagos para controle dos nematoides dos citros a campo. Foram monitoradas a sobrevivência dos fungos: Arthrobotrys robusta, A. oligospora, A. musiformis, Dactylella leptospora e Monacrosporium eudermatum nas parcelas tratadas com 1; 2; 4; 6 L da formulação dos fungos/planta ou testemunha sem aplicação, durante o período de nove meses, sendo a primeira avaliação 6 meses após a aplicação e as demais com intervalos de três meses após a primeira avaliação. O fungo D. leptospora foi encontrado somente na avaliação de 6 meses após a aplicação dos tratamentos, indicado um tempo de sobrevivência curto no solo. Contudo, os isolados A. robusta, A. musiformis e A. oligospora foram recuperados em todas as avaliações e principalmente nas parcelas tratadas com as maiores doses da formulação e na testemunha. Monacrosporium eudermatum foi recuperado em todos os períodos avaliados e inclusive na avaliação da parcela testemunha nove meses após a aplicação. O fato da presença das espécies de Arthrobotrys e M. eudermatum nas parcelas testemunhas indica que já eram espécies nativas desse pomar.
Survival of nematophagous fungi establishment of applied in the field for the control of key citrus nematodes in Brazil
Keywords: Biological management; Pratylenchus jaehni; Range of application; Tylenchulus semipenetrans; Arthrobotrys; Arthrobotrys musiformis; Arthrobotrys oligospora; Arthrobotrys robusta; Citrus; Fungi; Leptospora; Monacrosporium eudermatum; Monacrosporium leptosporum; Nematoda; Pratylenchus